THE BACKGROUND KNOWLEDGE AS AN EDUCATIONAL RESOURCE FOR STUDENTS TO MASTER TRANSLATION SKILLS OF DOCUMENTS IN CONSTRUCTION INDUSTRY - Шванова, Оксана Володимирівна; Рудіна, Марина Володимирівна (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2020)
It has been substantiated in the paper that the exercises on introduction of the terminology of the document “Energy performance certificate” on the topic “Construction” help to update the background knowledge of students as future translators. It is clarified that the background knowledge is a component of a translation competence, a resource of adequate translation of the specialist texts, a training resource for preparation of students as future translators, in “Construction” industry in particular. The following methods have been used: pedagogical observation for the well-directed investigation of background knowledge as a pedagogical phenomenon; concretization for the accurate characteristics of the document “Energy performance certificate”; generalization for specification of background knowledge while translating the documents in “Construction” industry; the pedagogical experiment – for the approbation of the special exercises on introduction of the terminology of the investigated document. On the basis of scientific research analysis on background knowledge in translation studies the practical exercises for students who learn to translate have been developed. It has been specified the role of the background knowledge in formation of the effective translation skills concerning the documents in “Construction” industry. It has been investigated that the exercises performance has increased the background knowledge of students on the topic “Construction”, influenced the quality of “Energy performance certificate” translation into Ukrainian. Studying the document “Енергетичний сертифікат будівлі” helped to provide the translation equivalents for the term combinations that was the main problem for students translating the document. It has been clarified the methodical aspect of the class: the introduction with the content of the document «Енергетичний сертифікат будівлі», finding out the meaning of lexical units, illustrative demonstration of their usage and combination with other lexical units in the translation text. It has been pointed out that the suggested exercises helped to avoid the semantic ambiguities in translation of “Energy performance certificate” into target language.